EFFECTIVE ASPECTS OF “GREEN ECONOMY” IN THE CONDITIONS OF UZBEKISTAN - Kuldashev Farid G‘ulom o‘g‘li; Radjabov Sherzod Umurzakovich (Journal Park Publishing, 2023)
One of the main goals of sustainable development is to preserve nature and its resources not only for today’s generation, but also for future generations. The full achievement of sustainable economic growth is gaining importance day by day. This requires the creation of foundations for socio-economic development based on the formation of new ideas and principles for sustainable development due to the creation of crisis situations of society in connection with the decrease in production, the decrease in the level of consumption of the population, the emergence of problem areas.